Chlamydomonas reinhardtii: duration of its cell cycle and phases at growth rates affected by light intensity - Vítová, Milada; Bišová, Kateřina; Umysová, Dáša; Hlavová, Monika; Kawano, Shigeyuki; Zachleder, Vilém; Cížková, Mária (Planta, 2011)
In the cultures of the alga Chlamydomonas reinhardtii, division rhythms of any length from 12 to 75 h were found at a range of different growth rates that were set by the intensity of light as the sole source of energy. The responses to light intensity differed in terms of altered duration of the phase from the beginning of the cell cycle to the commitment to divide, and of the phase after commitment to cell division. The duration of the pre-commitment phase was determined by the time required to attain critical cell size and sufficient energy reserves (starch), and thus was inversely proportional to growth rate. If growth was stopped by interposing a period of darkness, the pre-commitment phase was prolonged corresponding to the duration of the dark interval. The duration of the post-commitment phase, during which the processes leading to cell division occurred, was constant and independent of growth rate (light intensity) in the cells of the same division number, or prolonged with increasing division number. It appeared that different regulatory mechanisms operated through these two phases, both of which were inconsistent with gating of cell division at any constant time interval. No evidence was found to support any hypothetical timer, suggested to be triggered at the time of daughter cell release.
Keywords: cirkadiánní proteiny Period; časové faktory; Darkness; Light; Circadian Rhythm; mutace; Chlamydomonas reinhardtii; Cells, Cultured; cirkadiánní rytmus; Time Factors; Mutation; tma; světlo; buněčný cyklus; Cell Cycle; kultivované buňky; Period Circadian Proteins